(untitled) (GEON Journal (Management, Organizations and Business), 2018)
The planning of companies of the State involves a series of strategic guidelines that should reconcile the good administrative practices, as well as the assurance of the quality of the processes used to ensure that the use of public resources are used in the right way. The problem in the electricity sector in the Dominican Republic has forced the government to consider a scheme that allows you to provide a permanent solution to the difficulties of generation, purchase and distribution of energy, as well as the improvement of the service structure. For this was implemented in 2013 a new strategic planning model based on structural axes, which are analyzed in this article.